2017
DOI: 10.4067/s0718-221x2017005000008
|View full text |Cite
|
Sign up to set email alerts
|

Bondability of Black locust (Robinia pseudoacacia) and Beech wood (Fagus sylvatica) with polyvinyl acetate and polyurethane adhesives

Abstract: In the previous years, black locust wood (Robinia pseudoacacia) has been participating in the European subsidizing programme of tree species cultivation, aiming in the establishing of new plantations in many European countries, therefore large quantities of this species is going to be harvested in the forthcoming years and the examination of its properties would be very crucial for future utilization. In the present research, the bondability of black locust wood is examined using two different adhesives, Polyv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 8 publications
0
4
0
Order By: Relevance
“…Most of the research related to bonding of wood from alien invasive species in past was done only on more suitable and, in some countries, more common species, such as Robinia pseudoacacia (Konnerth et al 2016;Vasiliki and Ioannis 2017)) or Ailanthus altissima. Robinia pseudoacacia has been found to bond well with one-component polyurethane adhesives but has poor compatibility with phenol-resorcinol-formaldehyde adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the research related to bonding of wood from alien invasive species in past was done only on more suitable and, in some countries, more common species, such as Robinia pseudoacacia (Konnerth et al 2016;Vasiliki and Ioannis 2017)) or Ailanthus altissima. Robinia pseudoacacia has been found to bond well with one-component polyurethane adhesives but has poor compatibility with phenol-resorcinol-formaldehyde adhesives.…”
Section: Introductionmentioning
confidence: 99%
“…For example, they can be valorized in the construction sector as a reinforcement for polyurethane insulation materials thanks to their thermal and acoustic properties [3][4][5]. Polyurethane is also used in construction as an adhesive for aesthetic and structural applications [6]. However, given their origin from fossil oil, an alternative of bio-sourced products will be useful and appreciated by the market [7].…”
Section: Introductionmentioning
confidence: 99%
“…Polyurethane adhesives have been seen to lead to good joint strength; however, they can be sensitive to the moisture content of the wood and to temperature, showing worse bonding quality as the temperature increases and wood humidity decreases [ 21 , 22 ]. Vasiliki et al (2017) [ 23 ] analysed the bondability of a polyurethane adhesive and a polyvinyl acetatea adhesive by using black locust wood and beech wood substrates and concluded that pressure applied to the joint, regardless of adhesive and substrate, negatively influences shear bond strength, which was attrituted to the relation between the structure of the wood and its density and the characteristics of the adhesive, such as its viscosity and density. Additionally, it was noted that many factors can have an influence on the bondability of polyurethane adhesives and must be considered, such as wettability of the substrate surface and the ratio between the stiffness of the adhesive and substrate.…”
Section: Introductionmentioning
confidence: 99%